Pengaruh Kualitas Laba Dan Pengungkapan Sukarela Terhadap Cost of Equity Capital - Novia Yolanda; Erly Mulyani (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to determine and analyze the effect of earnings quality and voluntary disclosure on cost of equity capitalin manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017 both simultaneously and partially. The data analysis method used is panel data regression analysis. Using a purposive sampling method to get a sample of 71 companies from 213 manufacturing companies. Based on the results of the study it is known that the expertise of earnings quality and voluntary disclosure simultaneously influence the cost of equity capital. But partially, earnings quality has a positive effect on the cost of equity capitaland voluntary disclosure has a positive effect on the cost of equity capitalin manufacturing companies listed on the Indonesia Stock Exchange for the period 2015-2017